Asynchronous distributed localization in networks with communication delays and packet losses - Huang, Xu-Zhou; Tian, Yu-Ping (Automatica (Oxford), 2018)
This paper studies the problem of determining sensor locations in a large sensor network using only relative distance (range) measurement. Based on the barycentric coordinate representation, we propose a totally asynchronous distributed algorithm under DILOC framework due to independence of sensor update instants and unreliable networks with communication delays and packet losses. Through modeling the asynchronous algorithm as a linear difference equation with time-varying delays, we prove that the location estimates of sensors are globally convergent to the true coordinates if: (1) time interval between any two consecutive update instants is bounded from below and above, (2) communication delays and successive packet losses between sensors are finite. Simulation examples are provided to demonstrate the effectiveness of the theoretical result.